A New Version of Inextensible Flows of Spacelike Curves with Timelike B2 in Minkowski Space-Time E41 - Korpinar, Talat; Turhan, Essin (Springer India, 2013)
In this paper, we study inextensible flows of spacelike curves with timelike B-2 in the Minkowski space-time E-1(4). We give necessary and sufficient conditions for this inextensible flows. We derive the evolution equations for this inextensible flows in the Minkowski space-time E-1(4).
Keywords: Inextensible flows; Moving frame; Minkowski space time; Fluid flow